Atividade funcional da Na+K+-ATPase sensível à ouabaína em aorta de ratas com e sem sinais de insuficiência cardíaca após infarto do miorcárdio - Dias, Fernanda Moura Vargas (2007)
The identification of two distinct experimental groups (Icc – with, and Inf - without signals of heart failure (HF) folowing myocardial infarction in rats, presenting the same infarct area (IA), could explain, at least in part, the contradictory cardiovascular results in experimental models of HF. Recent research demonstrates the function of the Na+K + -ATPase in the vascular homostasis in the control of tonus. The activity of the Na+K + -ATPase is influenced by vasoativos factors endothelium-derivatives, cardiac glycosides, hormones, ionic concentration and shear stress, frequently altered after INF and HF. The objective of this research was to study the ouabain-sensitive Na+K + -ATPase functional activity in aortic rings of INF rats, with same IA, presenting or not signals of ICC. Female Wistar rats (220 ± 8 g), were distributed in: Sham (n= 13), Infarct without signals of ICC (Inf N = 11) and Infarct with signals of HF (Icc n= 7). MI was surgically induced by occluding left coronary artery. After 30 days the rats were anaesthetized, and the aortic rings was superfused with Krebs solution gasified with 95% O2 - 5% CO2 mixture to study rings with intact endothelium (E+), denuded endothelium (E -) and with L-NAME. The ouabain-sensitive Na+K + -ATPase functional activity was analized using the potassium relaxation technique. No differences was observed in IA (Inf: 30,2 ± 1,6; Icc: 35,6 ± 2,8), body weight (Sham: 236 ± 4 g; Inf: 236 ± 5 g; Icc: 235 ± 5 g) and VE/PC (Sham: 2,12 ± 0,05; Inf: 2,24 ± 0,06; Icc: 2,21 ± 0,07). However, the signals of HF appeared only in the Icc groups VD/PC (Sham: 0,6 ± 0,02; Inf: 0,6 ± 0,03; Icc: 1,4 ± 0,1* P<0.05) and PP/PC (Sham: 5,7 ± 0,3; Inf: 6,1 ± 0,3; Icc: 13,6 ± 1,0* P<0.05). The main results of this study are that in the Inf animals the KCl-induced relaxation was diminished and the endotelial modulation of this relaxation, for nitric oxide, was present. However, the capacity of the OUA to inhibit the Na+K + -ATPase was increased in these animals and it did not present endotelial modulation as seen in the groups Sham and Icc. These results demonstrate that OUA-dependent NO release is absent in the Inf group, but preserved in the Icc. Therefore, the results demonstrate for the first time in literature the participation of the Na+K + -ATPase in the changes of vascular reactivity following myocardial infarction in female rats. Moreover there are differences in the mechanisms involved in the aortic reactivity following myocardial infarction in female rats with same IA, presenting or not signals of HF.